DISEMINASI PENGETAHUAN DAN PERILAKU PENJAMAH MAKANAN DENGAN SANITASI PADA PROSES PRODUKSI MAKANAN DI INSTALASI GIZI RUMAH SAKIT UMUM DAERAH SEMBIRING - Reno Irwanto; Raini Panjaitan; Agnes Tresya Nababan (JURNAL PENGMAS KESTRA (JPK), 2021)
Sanitation is an effort to maintain health in the food sector through controlling environmental health, cleanliness of raw materials, workers, equipment and so on. Poor sanitation hygiene will have a major impact, especially in the field of nutrition in hospitals. Foods that have good nutritional components without attention to hygiene and sanitation will be less than optimal for the benefits felt by the body. This is because sanitation hygiene can reduce the value of the nutritional quality of the food components in question. This community service activity is carried out with the aim of providing knowledge of workers in the field of hospital nutrition in maintaining and maintaining the nutritional value of food to consumers and patients. This activity was carried out in November 2021 at the Sembiring Delitua General Hospital. This activity was carried out using lecture and interactive methods with 24 participants. The final result of the implementation of community service provided an increase in knowledge and awareness of the importance of sanitation for the participants by 26.17%. It is hoped that this activity can have a greater impact not only on workers, work units but also patients who visit the hospital.